Land Declaration Letter As Proof Of Ownership Of Land Rights (Case Study In Palangka Raya City) - Chairunisa, Arrum; Gusti Ayu Ketut Rachmi Handayani, I; Karjoko, Lego (International Journal of Educational Research & Social Sciences, 2023)
Land declaration (SPT) is the basic proof of ownership of a plot of land controlled by a person or legal entity. This right is generally used as a condition in the application process for the issuance of certificates of property rights by the National Land Agency. There are still many people who think that the Declaration of land owned is proof of ownership of land rights. It appears in many land cases in the judicial process. There are usually disputes between certificates and certificates, certificates and land certificates, or double certificates. However, the case that I take in this journal is taken from the decision of Case Number 160/Pdt.G / 2020 / PN Plk, which the judge declared valid and had legal force to bind the land declaration letter in the name of Mr. Basuki. Number: 140.594/300/KL-MTG/PEM Declaration of Land won from the Certificate of Title.. This study uses normative research methods that are accompanied by primary legal materials and secondary legal materials. To answer legal issues by describing, reviewing, reviewing, and explaining precisely and analyzing the applicable laws and regulations as well as from various legal expert opinions, in order to get answers to the problems raised.